DEVELOPMENT OF FLY ASH AND STEEL SLAG-BASED GEOPOLYMER CONCRETE TO REDUCE CARBON EMISSIONS IN CONSTRUCTION - Yehezkiel Septian Yoganata; Ikhsan Putra Pratama; Najla Nurrahma Amalia; Mohammad Amru Bil Ihsani; Kharisma Nur Cahyani; Nur Laily Lupita Sari (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
The global construction sector, particularly the production of concrete structures, is a major contributor to carbon dioxide (CO2) emissions. Portland cement alone is responsible for 10% of global emissions. In response to this sustainability issue, this research aims to develop green concrete through the partial substitution of cement using fly ash and fine aggregate with steel slag, based on the similarity of the chemical composition of these industrial wastes to concrete materials. The research focuses on two objectives: producing a concrete mix formula that meets the compressive strength standard of 21 MPa and comparing CO2 emissions level. The experiment was conducted in the laboratory in accordance with SNI 7656:2012, involving the fabrication of 24 cylindrical test specimens with three variations of fly ash substitution (10%, 15%, 20%) and steel slag substitution (20%, 15%, 10%). The 28-day compressive strength test results showed that all variations exceeded the strength of conventional concrete (22.29 MPa). Specifically, Variation II (15% fly ash, 15% steel slag) achieved optimal performance with a compressive strength of 24.91 MPa. In addition to its mechanical advantages, this optimal variation also reduced carbon emissions by 15%. These findings highlight the great potential of utilizing industrial waste in producing strong and environmentally friendly concrete.